pRB binds to and modulates the transrepressing activity of the E1A-regulated transcription factor p120(E4F) - Fajas, Lluis (The National Academy of Sciences, 2000)
The retinoblastoma protein pRB is involved in the transcriptional control of genes essential for cell cycle progression and differentiation. pRB interacts with different transcription factors and thereby modulates their activity by sequestration, corepression, or activation. We report that pRB, but not p107 and p130, binds to and facilitates repression by p120(E4F), a ubiquitously expressed GLI-Kruppel-related protein identified as a cellular target of E1A. The interaction involves two distinct regions of p120(E4F) and the C-terminal part of pRB. In vivo pRB–p120(E4F) complexes can only be detected in growth-arrested cells, and accordingly contain the hypophosphorylated form of pRB. Repression of an E4F-responsive promoter is strongly increased by combined expression of p120(E4F) and pRB, which correlates with pRB-dependent enhancement of p120(E4F) binding activity. Elevated levels of p120(E4F) have been shown to block growth of mouse fibroblasts in G(1). We find this requires pRB, because RB(−/−) fibroblasts are significantly less sensitive to excess p120(E4F).